THE IMPACT OF WORD OF MOUTH AND DISCOUNTS ON VISIT INTENTION WITH DESTINATION IMAGE AS INTERVENING ON TOURIST DESTINATIONS IN THE CITY OF BATAM - Rizni Aulia Qadri (Journal of Business Studies and Management Review, 2021)
The Covid-19 pandemic has greatly impacted sectors in all corners of the world, especially in Indonesia. Since the lockdown, the government has forced the country to lock up from tourists both foreign and domestic, a large-scale closure in Indonesia resulting in a very significant decline in the tourism sector. In the last few months tourism has reopened, so marketers are competing to attract visitors with interesting promotions and reviews related to the destination including the City of Batam. This research is classified as explanatory research, namely, research that explains the relationship variables and tests the relationship between several variables through testing several hypotheses using an approach with SmartPLS version 3 software with 390 respondents using the Hair calculation method. The results of this study indicate that Destination image, Word of Mouth, and Discount has a significant positive effect on visit intention.